Mode of action and dose–response framework analysis for receptor-mediated toxicity: The aryl hydrocarbon receptor as a case study. (January 2014) - Budinsky, R. A.; Schrenk, D.; Simon, T.; Van den Berg, M.; Reichard, J. F.; Silkworth, J. B.; Aylward, L. L.; Brix, A.; Gasiewicz, T.; Kaminski, N.; Perdew, G.; Starr, T. B.; et al.
Abstract Dioxins and dioxin-like compounds are tumor promoters that cause liver cancer in rats and mice. The aryl hydrocarbon receptor (AHR) has been implicated as a key component in this tumor promotion response. Despite extensive knowledge of the toxicology of dioxins, no mode of action (MOA) hypothesis for their tumorigenicity has been formally documented using the Human Relevance MOA framework developed by the International Programme on Chemical Safety (IPCS). To address this information gap, an expert panel was convened as part of a workshop on receptor-mediated liver tumorigenicity. Liver tumors induced by ligands of the AHR were assessed using data for dioxins and related chemicals as a case study. The panel proposed a MOA beginning with sustained AHR activation, eventually leading to liver tumors via a number of other processes, including increased cell proliferation of previously initiated altered hepatic foci, inhibition of intrafocal apoptosis and proliferation of oval cells. These processes have been identified and grouped as three key events within the hepatocarcinogenic MOA: (1) sustained AHR activation, (2) alterations in cellular growth and homeostasis and (3) pre-neoplastic tissue changes. These key events were identified through application of the Bradford-Hill considerations in terms of both their necessity for the apical event/adverse outcome and their human relevance. The panel identified data supporting the identification and dose–response behavior of key events, alteration of the dose–response by numerous modulating factors and data gaps that potentially impact the MOA. The current effort of applying the systematic frameworks for identifying key events and assessing human relevance to the AHR activation in the tumorigenicity of dioxins and related chemicals is novel at this time. The results should help direct future regulatory efforts and research activities aimed at better understanding the potential human cancer risks associated with dioxin exposure.